2017
DOI: 10.1007/s12603-017-0906-3
|View full text |Cite
|
Sign up to set email alerts
|

Late-life body mass index, rapid weight loss, apolipoprotein E ε4 and the risk of cognitive decline and incident dementia

Abstract: Purpose of the study To examine the effect of late-life body mass index (BMI) and rapid weight loss on incident mild cognitive impairment (MCI) and Alzheimer’s disease (AD) Design Prospective longitudinal cohort study Setting National Alzheimer’s Coordinating Center (NACC) Uniform Data Set, including 34 past and current National Institute on Aging-funded AD Centers across the United States Participants 6940 older adults (n=5061 normal cognition (NC); n=1879 MCI) Measurements BMI (kg/m2) and modified Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 53 publications
7
35
0
6
Order By: Relevance
“…The association between BMI in late life and CD has been controversial . While some studies observed that higher BMI is linked with increased risk of dementia, others found an inverse association in elders, consistent with our findings. More research examining the association BMI between CD is needed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The association between BMI in late life and CD has been controversial . While some studies observed that higher BMI is linked with increased risk of dementia, others found an inverse association in elders, consistent with our findings. More research examining the association BMI between CD is needed.…”
Section: Discussionsupporting
confidence: 90%
“…The association between BMI in late life and CD has been controversial. 48 While some studies observed that higher BMI is linked with increased risk of dementia, 49 others found an inverse association in elders, 50 relationships between specific domains of cognitive function and SN types. Forth, we did not include persons who died or dropped out of the survey.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that long-term intake of high-fat diets, even in the absence of obesity, leads to cognitive deficits (Cifre, Palou, & Oliver, 2018). One study indicates that obesity may increase the risk for AD by twofold (Salas et al, 2018), whereas other studies report that a higher BMI is associated with a lower risk of cognitive deficits (Bell et al, 2017;Cova et al, 2016) and that a lower BMI contributes to cognitive impairment (Mathys, Gholamrezaee, Henry, von Gunten, & Popp, 2017;Pilleron et al, 2015). Another study showed that participants with a baseline BMI ≥ 25 kg/m 2 had significantly higher MMSE scores compared with participants with BMI < 25 kg/m 2 (Coin et al, 2012).…”
Section: Ta B L E 3 Relevance Between 3-month Mmse Scores and Baselinmentioning
confidence: 99%
“…This mechanism is not fully understood because fat tissue simultaneously produces soluble receptors for TNFα (srTNFα), which can neutralise the secreted TNFα. This phenomenon is the subject of numerous discussions which try to explain the better prognosis of obese elderly people with cardiovascular diseases [28,29].…”
Section: Paradoks Otyłościmentioning
confidence: 99%
“…Mechanizm ten nie został do końca poznany, ponieważ tkanka tłuszczowa produkuje równocześnie rozpuszczalne receptory dla TNF-α (srTNFα), które mogą neutralizować wydzielany TNF-α. Zjawisko to jest przedmiotem licznych dyskusji, które próbują wyjaśnić lepsze rokowanie otyłych osób starszych z chorobami układu krążenia [28,29].…”
Section: Weight Loss As a Medical Recommendationunclassified